Growth responses in Swedish boreal coniferous forests after addition of nitrogen as sewage sludge pellets - Kovanen, Maija (2007)
Every year, large amounts of municipal sewage sludge are produced worldwide. Most of the sludge ends up on landfills, garbage dumps and incineration plants, and only small part is utilized as a fertilizer in agriculture and forestry. Sewage sludge contains a lot of nutrients, especially nitrogen. In boreal forests, a lack of available nitrogen limits the growth, and therefore sewage sludge could be applied into forests to increase the growth. Sewage sludge pellets might offer a good alternative for liquid and dewatered sludge or even for inorganic fertilizers in fertilizing forests. The aims of this study were to investigate the effect of the addition of nitrogen as sewage sludge pellets on tree growth, the effect of dose size and the duration of the growth response.